A FEM and Image Processing Based Method for Simulation of Manufacturing Imperfections - Javed, Arshad; Sengar, A. K.; Rout, B. K. (Asian Review of Mechanical Engineering, 2012)
Use of appropriate methods to capture manufacturing imperfection at the conceptual stage is a major challenge for the designer and researchers in industry. Imperfections are observed in almost all type of in macro, micro and nano-machining domain of manufacturing process. These imperfections lead to undesirable performance in application phase. In the present work, a simulation based approach to handle manufacturing imperfection is implemented using image processing operators. This method simulates the image of the component due to manufacturing imperfections. The usage of these image processing operators facilitates a realistic simulation of manufacturing errors, in macro, micro, and nano domain manufacturing. The simulated image is further processed for its structural properties i.e. maximum deflection, reactions, Von Mises stress, and change in amount of material, corresponding to its intended application. In order to generate these results based on modified image of beam, the concept of “Solid Isotropic Material with Penalization”(SIMP) is utilized along with 2-D finite element routine. An example of a simple cantilever beam is selected to illustrate the proposed methodology, and the results are analyzed. The present work discusses a simple and easy method to predict the behavior of designed component prior to its manufacturing.